Pseudo-differential operators of infinite order on (Formula presented.)-space involving fractional Fourier transform - Upadhyay S.K.; Dubey J.K. (My University, 2025)
The mapping properties of pseudo-differential operators associated with symbol (Formula presented.) and (Formula presented.) on (Formula presented.)-space are investigated. Motivated from Wong (An introduction to pseudo-differential operators. World Scientific, Singapore, 2014), (Formula presented.)-boundedness of pseudo-differential operators on (Formula presented.)-space is studied by using the fractional Fourier transform. © 2015, Springer Basel.